Accuracy in perceptions of a partner's sexual goals. (May 2022) - Elsaadawy, Norhan; Impett, Emily A.; Raposo, Stephanie; Muise, Amy
Intimate partners engage in sex for a variety of reasons, and their perceptions of each other's sexual goals play an important role in intimate relationships. How accurate are these perceptions of a partner's sexual goals and is accuracy associated with relationship quality and sexual satisfaction for the couple? To answer these questions, we conducted a 21-day dyadic daily experience study of 121 couples, which we analyzed using two different approaches to examine accuracy: the profile approach and the Truth and Bias Model. Results from these two approaches demonstrated that people's perceptions of their partner's sexual goals were indeed accurate, but that accuracy was not associated with relationship quality or sexual satisfaction for the perceiver or their partner. Rather, perceiving a partner's sexual goals in normative (or socially desirable) ways was associated with relationship quality and sexual satisfaction for both the perceiver and their partner. Implications of these findings are discussed.